Factor analyses of multidimensional symptoms in a large group of patients with major depressive disorder, bipolar disorder, schizoaffective disorder and schizophrenia - Stein, Frederike; Lemmer, Gunnar; Schmitt, Simon; Brosch, Katharina; Meller, Tina; Fischer, Elena; Kraus, Cynthia; Lenhard, Lutz; Köhnlein, Birgit; Murata, Harumi; Bäcker, Achim; Müller, Matthias; et al. (Schizophrenia research, 2020)
There is an ongoing discussion about which neurobiological correlates or symptoms separate the major psychoses (i.e. Major Depressive Disorder MDD, Bipolar Disorder BD, and Schizophrenia SZ). Psychopathological factor analyses within one of these disorders have resulted in models including one to five factors. Factor analyses across the major psychoses using a comprehensive set of psychopathological scales in the same patients are lacking. It is further unclear, whether hierarchical or unitarian models better summarize phenomena. Patients (n = 1182) who met DSM-IV criteria for MDD, BD, SZ or schizoaffective disorder were assessed with the SANS, SAPS, HAMA, HAM-D, and YMRS. The sample was split into two and analyzed using explorative and confirmatory factor analyses to extract psychopathological factors independent of diagnosis. In the exploratory analysis of sample 1 (n = 593) we found 5 factors. The confirmatory analysis using sample 2 (n = 589) confirmed the 5-factor model (χ2 = 1287.842, df = 571, p < .0001: CFI = 0.932; RMSEA = 0.033). The 5-factors were depression, negative syndrome, positive formal thought disorder, paranoid-hallucinatory syndrome, and increased appetite. Increased appetite was not related to medication. None of the factors was specific for one diagnosis. Second order factor analysis revealed two higher order factors: negative/affective (I) and positive symptoms (II). This is the first study delineating psychopathological factors in a large group of patients across the spectrum of affective and psychotic disorders. In future neurobiological studies, we should consider transdiagnostic syndromes besides the traditional diagnoses.